Uporządkuj jednomiany.
a) 3axyb=
b) -3bxa * y * 2 =
c) (-2) *(-a) * (-x) * (-b) * (-3) * 2=
d) x * a * a (-3/4) * 2 * x(-b)
e) y * 2(do potęgi 2 ) * 2,5 * (-1) * a * y * 3x(do potęgi 2 )
f) 2/5 * 3/4 * x * * b * a(do potęgi 2 ) * (-1) * x(do potęgi 2 ) (-b) =


proszę o pomoc jak najszybciej ;))))

prosze .... z gory dziekuje :)

1

Odpowiedzi

2010-01-27T17:43:38+01:00
A 3abxy
b -6abxy
c 12a(do potegi 2)bx
d -1,5a(do potegi 2)bx(do potegi 2)
e -30ax(do potegi 2)y(do potegi 2)
f 0,3a(do potegi 2)b(do potegi 2)x(do potegi 3)